Chemiresistive gas sensor based on electrospun hollow SnO2 nanotubes for detecting NO at the ppb level. (May 2022) - Su, Peng; Li, Wei; Zhang, Jie; Xie, Xiaoling
Abstract: Detecting some appropriate target gases through the optimization of material structure is still applicable to some old sensing materials. In this work, we showed that hollow tin oxide (SnO2 ) nanotubes (NTs) exhibited a remarkable sensing performance for nitric oxide (NO) at 160 °C. The sensing materials were prepared by direct annealing of electrospun precursor nanofibers, and hollow NTs can be obtained at an appropriate heating rate of 6 °C/min. Given the large surface area of hollow SnO2 NTs, their sensing performance is better than that of solid SnO2 NTs. The response of hollow SnO2 NTs is approximately 33.3 upon exposure to 500 ppb of NO at 160 °C. The hollow SnO2 NTs also exhibit good repeatability, long-term stability, and excellent selectivity. These remarkable sensing properties indicate that conventional SnO2 still has great practical applications because of the fine design of the material structure and proper control of working conditions. Highlights: Hollow SnO2 nanotubes can be prepared by the calcination of precursor nanofibers with a suitable heating rate. Hollow SnO2 nanotubes possess higher surface area and more surface-adsorbed oxygen species than solid nanotubes. Hollow SnO2 nanotubes can detect NO gas down to 10 ppb. Hollow SnO2 nanotubes show good reproducibility, long-term stability, and excellent selectivity.